EmilyJernigan 3 years ago Use the Quadratic Formula to solve the equation. -2x^2 - 5x + 5 = 0

1. Calcmathlete

$\LARGE Quadratic~Formula: x = \frac{-b ± \sqrt{b^2 - 4ac}}{2a}$$\large where,$$\large a = -2$$\large b = -5$$\large c = 5$

2. lopez_hatesmath
3. waleed_imtiaz

$x= -b \pm \sqrt{b^{2}-4ac}/2a$ put the values

4. EmilyJernigan

Lopez.. my answers dont look like that on the site

5. EmilyJernigan

I still dont know how to do this.:/

6. satellite73

$-2x^2 - 5x + 5 = 0$multiply by $$-1$$ to make life nicer get $2x^2 + 5x - 5 = 0$use $x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$ with $a=2,b=-5,c=5$

7. satellite73

put the numbers in the slot,s, do the arithmetic carefully $x=\frac{-(-5)\pm\sqrt{(-5)^2-4\times 1\times 5}}{2\times 2}$

8. lopez_hatesmath

9. lopez_hatesmath

i got x approx -3.26556 and x approx 0.765564

10. EmilyJernigan

I tried to work it out and i still dont see my answer'

11. EmilyJernigan

|dw:1344713909733:dw| My answers look like this

12. lopez_hatesmath

13. EmilyJernigan

That was A... hold on.

14. lopez_hatesmath

-5+or- sqrt of 5 all over 2

15. EmilyJernigan

|dw:1344714110752:dw|

16. EmilyJernigan

Thats not an option

17. Calcmathlete

$\implies x = \frac{-(-5) ± \sqrt{(-5)^2 - 4(-2)(5)}}{2(-2)}$$\implies x = \frac{5 ± \sqrt{25 + 40}}{-4}$$\implies x = -\frac{5 ± \sqrt{65}}{4}$$\implies x = -\frac54 ± \frac{\sqrt{65}}{4}$Do you see how I got that based on my first post?

18. EmilyJernigan

I think so. Thank you!

19. Calcmathlete

np :)

20. lopez_hatesmath

swaggg